Mapping national anxieties Thailand's Southern conflict - McCargo, Duncan (Copenhagen : NIAS Press, 2012)
"Mapping National Anxieties locates the insurgency in the context of Thailand's wider political conflicts, exploring the ambiguous relationships between the Thai state and organised religion, the recent resurgence of Buddhist chauvinism and nationalism. McCargo examines the way Islamic provincial councils have been drawn into the conflict, and scrutinises the special challenges the conflict has created for Thailand's media, which have struggled to communicate a confusing story to an increasingly indifferent wider public. The book then moves beyond the crisis itself to look at ways forward, starting with the controversial National Reconciliation Commission that was established by the Thaksin Shinawatra government to propose peaceful options for reducing the violence. Another chapter explores how far Malay Muslims in Thailand's southern border provinces think of themselves as 'Thai', arguing that there is an important distinction between legal citizenship and informal understandings of what citizenship means and entails. Finally, McCargo invites readers to 'think the unthinkable' by imagining the possibility of autonomy for Thailand's deep South, and the implications for the country as a whole."--P. [4] of cover.
Mapping anxieties -- Buddhist fears -- Managing Islam -- National reconciliation -- Communicating conflict -- Contested citizenship -- Autonomous futures -- Twin fires.
Includes bibliographical references (p.187-202) and index.
Description based on print version record.
Keywords: Insurgency -- Thailand, Southern; Political violence -- Thailand, Southern; Religion and state -- Thailand, Southern; Muslims -- Political activity -- Thailand, Southern; Buddhists -- Political activity -- Thailand, Southern; Thailand -- Politics and government -- 1988-; Thailand, Southern -- History -- Autonomy and independence movements; Aufstand; Religion; Thailand (Süd); HISTORY / Asia / Southeast Asia; Electronic books